Cardioprotective Role of BGP-15 in Ageing Zucker Diabetic Fatty Rat (ZDF) Model: Extended Mitochondrial Longevity - Mate Kozma; Mariann Bombicz; Balazs Varga; Daniel Priksz; Rudolf Gesztelyi; Vera Tarjanyi; Rita Kiss; Reka Szekeres; Barbara Takacs; Akos Menes; Jozsef Balla; Gyorgy Balla; et al. (MDPI AG, 2022)
Impaired mitochondrial function is associated with several metabolic diseases and health conditions, including insulin resistance and type 2 diabetes (T2DM), as well as ageing. The close relationship between the above-mentioned diseases and cardiovascular disease (CVD) (diabetic cardiomyopathy and age-related cardiovascular diseases) has long been known. Mitochondria have a crucial role: they are a primary source of energy produced in the form of ATP via fatty acid oxidation, tricarboxylic acid (TCA) cycle, and electron transport chain (ETC), and ATP synthase acts as a key regulator of cardiomyocyte survival. Mitochondrial medicine has been increasingly discussed as a promising therapeutic approach in the treatment of CVD. It is well known that vitamin B3 as an NAD+ precursor exists in several forms, e.g., nicotinic acid (niacin) and nicotinamide (NAM). These cofactors are central to cellular homeostasis, mitochondrial respiration, ATP production, and reactive oxygen species generation and inhibition. Increasing evidence suggests that the nicotinic acid derivative BGP-15 ((3-piperidine-2-hydroxy-1-propyl)-nicotinic amidoxime) improves cardiac function by reducing the incidence of arrhythmias and improves diastolic function in different animal models. Our team has valid reasons to assume that these cardioprotective effects of BGP-15 are based on its NAD+ precursor property. Our hypothesis was supported by an animal experiment where ageing ZDF rats were treated with BGP-15 for one year. Haemodynamic variables were measured with echocardiography to detect diabetic cardiomyopathy (DbCM) and age-related CVD as well. In the ZDF group, advanced HF was diagnosed, whereas the BGP-15-treated ZDF group showed diastolic dysfunction only. The significant difference between the two groups was supported by post-mortem Haematoxylin and eosin (HE) and Masson's trichrome staining of cardiac tissues. Moreover, our hypothesis was further confirmed by the significantly elevated Cytochrome c oxidase (MTCO) and ATP synthase activity and expression detected with ELISA and Western blot analysis. To the best of our knowledge, this is the first study to demonstrate the protective effect of BGP-15 on cardiac mitochondrial respiration in an ageing ZDF model.